2019
DOI: 10.7759/cureus.6183
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status in Pregnant Women and Sleep Quality During Pregnancy

Abstract: Silva-perez et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 3.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
(43 reference statements)
1
17
0
8
Order By: Relevance
“…It must also be taken into consideration that there are some other aspects influencing sleep and that it is affected by different psychological and environmental factors such as socioeconomic status [ 59 , 60 ]. There is also a reverse relationship, as sleep deprivation can lead to decreased quality of life, deterioration in energy to perform everyday activities and inability to work [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It must also be taken into consideration that there are some other aspects influencing sleep and that it is affected by different psychological and environmental factors such as socioeconomic status [ 59 , 60 ]. There is also a reverse relationship, as sleep deprivation can lead to decreased quality of life, deterioration in energy to perform everyday activities and inability to work [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while our data suggest a strong association between the economic strength and the OSA activity on country level, recent studies have also taken into account the complex interplay between the individual socioeconomic status (SES) and sleep disorders. A growing body of literature of different population subgroups [53] is elucidating the role of a low SES on sleep outcomes such as insomnia, excessive daytime sleepiness, and sleep efficiency [54,55]. However, to date, only limited studies have evaluated the associations between SES and OSA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, poor quality sleep and insomnia have a tight connection with emotions. Previous studies have observed the implications of loneliness, grief, hostility, impulsivity, stress, depression, and anxiety in terms of sleep [1,9,10,11]. The close-knit relationship displayed between emotion and sleep is gradually being distinguished as a crucial area for research [12].…”
Section: Introductionmentioning
confidence: 99%